Changes of power and regional organizations in the post-Soviet space and Latin America - Gallegos Pazmiño, César Francisco (Universidad Nacional del Litoral, 2020)
The article explores how power shifts in global politics and the emergence of regional powers affect regional security governance. The post-Soviet space and Latin America are identified as two regions where the hegemonic and Cold War powers (the United States and Russia) have recently been challenged by already affirmed or rising powers (Brazil and China, respectively). In both regions, there is an older regional organization shaped by the dynamics of the Cold War along with a newer organization formed by the growing power. But do similar patterns of power shifts lead to similar types and trajectories of security governance? Four security organizations from the two regions are analysed: the Organization for Security and Cooperation in Europe (OSCE) and the Shanghai Cooperation Organization (SCO) from the post-Soviet space; and the Organization of American States (OAS) and the Union of South American Nations (UNASUR) of Latin America. It shows how changes in power are reflected in (1) the factors that drive the foundation and transformation of the organization, (2) the organizations' security conceptions and practices, and (3) organizational overlap.